2021
DOI: 10.3762/bjoc.17.78
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free glycosylation with glycosyl fluorides in liquid SO2

Abstract: Liquid SO2 is a polar solvent that dissolves both covalent and ionic compounds. Sulfur dioxide possesses also Lewis acid properties, including the ability to covalently bind Lewis basic fluoride ions in a relatively stable fluorosulfite anion (FSO2 −). Herein we report the application of liquid SO2 as a promoting solvent for glycosylation with glycosyl fluorides without any external additive. By using various temperature regimes, the method is applied for both armed and disarmed glucose and mannose-derived gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Heating a solution of thionyl fluoride dissolved in DMF to 130 °C resulted in the formation of FSO 2 − , indicated by a signal at +36 ppm by 19 F NMR spectroscopy. 22 The presence of FSO 2 − confirmed that deoxygenation of DMF was occurring within our reaction system forming either compound 5 or 7 (Scheme 2a).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Heating a solution of thionyl fluoride dissolved in DMF to 130 °C resulted in the formation of FSO 2 − , indicated by a signal at +36 ppm by 19 F NMR spectroscopy. 22 The presence of FSO 2 − confirmed that deoxygenation of DMF was occurring within our reaction system forming either compound 5 or 7 (Scheme 2a).…”
supporting
confidence: 54%
“…Heating a solution of thionyl fluoride dissolved in DMF to 130 1C resulted in the formation of FSO 2 À , indicated by a signal at +36 ppm by 19 F NMR spectroscopy. 22 The presence of Yields determined by 19 F NMR spectroscopy at 0.25 mmol. a Equivalents of thionyl fluoride gas dissolved in DMF.…”
mentioning
confidence: 99%
“…À as the only compounds visible by 11 B NMR. 19 F NMR of the same extracts confirmed the presence of these species along with a small amount of SO 2 F À [41] and other unidentified peaks. HRMS analysis confirmed the presence of fluorosulfite ions and several several fluoroborates (BF(OH) 3 À , BF 2 (OH) 2 À , BF 3 (OH) À , BF 4…”
Section: Methodsmentioning
confidence: 74%
“…Turks and co-workers have recently identified SO 2 as both a solvent and as an activator of glycosyl fluorides, 64 which also gave rise to the discovery of a remarkable vessel effect. Whereas mannosylations proceeded in high yields at 100 °C in SO 2 , a comparable experiment in a PTFE vessel only resulted in 8% yield of the desired product and recovery of 53% of the electrophile.…”
Section: C–f Bond Activationmentioning
confidence: 99%